Peran Online Travel Agent Dalam Meningkatkan Penjualan Kamar Pada Hotel Swiss Belinn Karawang - Sinta Murti Cahyani; Uus Mohammad Darul Fadli (Global Leadership Organizational Research in Management, 2024)
This research aims to determine the role of online travel agents (OTA) in increasing room sales at the Swiss-Belinn Karawang Hotel. In an increasingly competitive hotel industry, collaboration with OTA platforms has become an important strategy to expand market reach and increase occupancy rates. This study uses a qualitative analysis method by collecting interviews and surveys from hotel management and guests. The research results show that collaboration with OTAs significantly increases the visibility of hotels in the global market, reduces marketing costs, and increases occupancy rates through increasing the number of bookings. In addition, an efficient inventory management system and positive reviews from guests on the OTA platform contribute to the optimization of the hotel's revenue and reputation. Thus, OTA plays an important role in the marketing and sales strategy of Hotel Swiss-Belinn Karawang, which directly impacts increasing room sales and overall hotel business growth. This research suggests that hotels should continue to strengthen partnerships with OTAs and optimize the use of data and technology provided by these platforms to achieve better results in the future.